Attitudes of non-native students towards learning English as a foreign language: a case study in secondary schools in the Sultanate of Oman - Alsoudi, Sharif; Al Harthy, Salim; Al Harthy, Azza; Al Harthy, Zainah (Frontiers in Education, 2024)
Attitudes are crucial in education, impacting students’ motivation, engagement, and achievement. This study explored Omani high schoolers’ attitudes towards learning English and the differences in their attitudes per their demographics and other variables. The Attitudes Toward English scale was used with 576 students. The findings showed that the students’ attitudes were mildly positive and that significant differences also emerged. Private school and science-track students showed more positive attitudes than government school and humanities students. Supplementary training also improved their attitudes, and parental education levels positively predicted their attitudes. More favorable attitudes strongly correlated with higher English achievement, indicating a need to nurture positive perspectives. The study provided insights into Omani students’ attitudes toward English and showed that fostering positivity might enhance students’ motivation, proficiency, and outcomes. Further research can evaluate interventions for shaping students’ constructive attitudes.